2014
DOI: 10.1007/s12072-014-9598-5
|View full text |Cite
|
Sign up to set email alerts
|

High rate of core promoter and precore mutations in patients with chronic hepatitis B

Abstract: BackgroundThe prevalence of precore (PC) and core promoter (CP) mutations in patients with chronic hepatitis B virus (HBV) infection (CHB) and their impact on liver disease is incompletely defined in the United States.MethodsA retrospective chart review using a cross-sectional approach of 1,186 CHB patients was conducted.ResultsOf 926 patients tested for HBV e antigen (HBeAg), 37 % were HBeAg+. Of 194 patients tested for mutations, 80 % had PC or CP mutations or both; 89 % of HBeAg-negative and 56 % of HBeAg+ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…However, for some patients the infecting virus strain mutate in the pre-core region to form the so-called pre-core mutant [12] or in the basal core promoter region [13, 14]. Patients infected with these mutants often have active liver disease with elevated HBV DNA levels in serum also after seroconversion to anti-HBe [15, 16].…”
Section: Introductionmentioning
confidence: 99%
“…However, for some patients the infecting virus strain mutate in the pre-core region to form the so-called pre-core mutant [12] or in the basal core promoter region [13, 14]. Patients infected with these mutants often have active liver disease with elevated HBV DNA levels in serum also after seroconversion to anti-HBe [15, 16].…”
Section: Introductionmentioning
confidence: 99%
“…Chronic hepatitis leads to necroinflammation and fibrosis progression, and increases the risk of developing cirrhosis and hepatocellular carcinoma. 297 mutations(Baqai et al, 2015; Chu et al, 2003; Takahashi et al, 298 1995) which transitions later to a dominant, but not pure, HBeAg(À) disease. If infection is transmitted from a person with 300 mixed infection, the person who becomes infected (for example, 301 the child in mother-to-child transmission) develops HBeAg(+) non-replicative phase characterized by normal ALT and low or 309 undetectable HBV DNA or transition directly to HBeAg(À) CHB.…”
mentioning
confidence: 99%
“…The 1762 and 1764 mutations reduce transcription of the PC mRNA by interfering binding of transcription factors, which in turn downregulates HBeAg synthesis. Some studies have shown that genomic mutations at positions 1727G, 1741C, 1761C, 1757A /1764T /1766G, 1773T, 1773T /1775G and 1909C are associated with HCC in HBV-infected patients (15)(16)(17)(18)(19). Several studies have reported an association between CP mutations and increased risk of liver inflammation, cirrhosis (20) and HCC (21).…”
Section: Resultsmentioning
confidence: 99%
“…The other hotspot CP mutations are 1753A/C/G and 1768A, which are also associated with the increased risk of HCC. BCP mutations are common in HCC patients and there is a high rate of point mutations in this region (particularly dual V131L and K130M) among patients with cirrhosis and HCC (18,(25)(26)(27). In our study, we identified these mutations in two patients that can be indicator of HCC progression.…”
Section: Discussionmentioning
confidence: 99%